Translucent barriers that GAFTA award holders encounter when seeking to enforce them: the public policy exception as GAFTA’s Achilles heel - Benavente Norza, Mónica (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Compared to awards from other arbitration bodies, obtaining a GAFTA award offers the prevailing party added value by increasing commercial pressure on the defaulters via the publication of unpaid award references and defaulters’ names on a defaulter list. However, in cases in which a defaulter still refuses to honour their obligations under an award, the winning party has no option but to enforce the award under the umbrella of the New York Convention. In these cases, defaulters frequently raise the public policy exception in an attempt to hamper the execution of the award or to make it very expensive and time-consuming. This paper seeks to better comprehend the reasons behind this situation and proposes alternatives for improving it.
Keywords: Arbitration; GAFTA; New York Convention; Enforcement; Public Policy